Effects on heart rate variability of a European under-18 rugby tournament - Solís-Mencía, C.; Jiménez-Herranz, E.; Cano-Cappellacci, M.; Ibacache-Saavedra, P.; García-Fernández, P.; de Sousa-De Sousa, L.; Ramos Veliz, R.; De Matías-Cid, P.; Ramos-Álvarez, J. J. (The Journal of Strength and Conditioning Research, 2026)
Rugby union is characterized by intermittent efforts combining high and lowintensity actions. In European Under-18 Rugby XV Championship, matches are played every 72 hours, which may hinder adequate recovery. Heart rate variability (HRV) is a noninvasive method that assesses the autonomic nervous system activity, yet its role to measure the rugby players recovery remains underexplored. The purpose of this study was to evaluate HRV responses in elite under-18 rugby players during an European Championship with matches every 72 hours. This prospective study was conducted with 27 players from the Spanish under-18 national rugby team. HRV data were collected daily for 12 days, including pretournament preparation and 3 matches. Measurements were taken in a supine resting position using a Bluetooth chest-strap. Time-domain, frequency-domain, and nonlinear HRV metrics were analyzed. Statistical comparisons were made using Friedman and Wilcoxon tests (p < 0.05). HRV metrics showed no significant differences between pretournament values and the first match day (first MD). However, time-domain, frequency-domain, and nonlinear variables significantly decreased after the first MD compared with the second (second MD) and third match days (third MD) (p < 0.0001). No significant differences were observed between the second MD and third MD. These findings suggest persistent autonomic imbalance and insufficient recovery between matches. Playing matches every 72 hours does not allow for adequate recovery in under-18 rugby players. Daily HRV monitoring provides a valuable tool for assessing fatigue, guiding training load management, and reducing injury risk during competitive tournaments.